Reinventing Global Trends Approach In Building A World Class University: Implementation Study At Lambung Mangkurat University - Mutiani Mutiani; Atiek Winarti; Irham Taufiqurrahman; Rizky Amelia; Herry Setiawan (Universitas Lambung Mangkurat, 2025)
The era of rapid globalization has increased the importance of human resource (HR) management in higher education institutions to achieve international competitiveness. Universitas Lambung Mangkurat (ULM), a state university in South Kalimantan, Indonesia, has embarked on a transformation journey towards becoming a World Class University (WCU) by aligning its strategy to the stringent criteria of the QS World University Rankings. This study examines ULM's HR development initiatives and strategic approaches to meet global standards while addressing local challenges. Using a SWOT analysis, this study highlights ULM's strengths, including its focus on locally-based research, such as wetland studies, and strong institutional support. However, significant weaknesses hinder progress, such as the limited number of doctoral-qualified lecturers and the low rate of international publications. Opportunities for international collaboration and global research funding indicate potential for strategic partnerships.Meanwhile, threats such as intense competition and fluctuating education policies demand adaptive strategies. The integration of international collaboration, digitalization, and capacity-building programs for ULM lecturers has shown promising results, as evidenced by the increasing partnerships with universities. ULM seeks to balance the dual mandate of global competitiveness and local community impact by harnessing unique local potential and aligning it with global trends. This research provides valuable insights into strategic human resource management and policy implications for universities aspiring to achieve WCU status while remaining relevant to regional needs.